2018
DOI: 10.1210/jc.2017-02419
|View full text |Cite
|
Sign up to set email alerts
|

Metformin Use in PCOS Pregnancies Increases the Risk of Offspring Overweight at 4 Years of Age: Follow-Up of Two RCTs

Abstract: Metformin-exposed children had higher BMI and increased prevalence of overweight/obesity at 4 years of age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
116
0
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(128 citation statements)
references
References 39 publications
4
116
0
8
Order By: Relevance
“…Nadalje, gotovo polovici trudnica s GDM-om koje su u početku liječene metforminom treba terapija inzulinom za postizanje zadovoljavajuće glukoregulacije 31 . Ipak, ono što najviše zabrinjava kada je u pitanju primjena metformina u trudnoći, jesu podaci koji ukazuju na veću pojavnost debljine u djece čije su majke tijekom trudnoće uzimale metformin 32,33 .…”
Section: Oralni Antihiperglikemiciunclassified
“…Nadalje, gotovo polovici trudnica s GDM-om koje su u početku liječene metforminom treba terapija inzulinom za postizanje zadovoljavajuće glukoregulacije 31 . Ipak, ono što najviše zabrinjava kada je u pitanju primjena metformina u trudnoći, jesu podaci koji ukazuju na veću pojavnost debljine u djece čije su majke tijekom trudnoće uzimale metformin 32,33 .…”
Section: Oralni Antihiperglikemiciunclassified
“…7 Recent data suggest significantly increased rates of overweight and obesity in a cohort of 4-year-old children of mothers with polycystic ovarian syndrome who were exposed to metformin during pregnancy compared to the offspring of non-exposed women. 8 Women of childbearing age with T2DM are now frequently treated with newer oral diabetes therapies such as dipeptidyl peptidase-4 (DPP-4) inhibitors and sodium glucose co-transporter 2 (SGLT-2) inhibitors. In general, preclinical reproduction studies using DPP-4 inhibitors in rats have provided no evidence of impaired fertility or teratogenicity.…”
Section: Introductionmentioning
confidence: 99%
“…10 In addition, metformin use in PCOS pregnancies is associated with a higher risk for the child of being overweight at the age of 4 years. 11 In obese women, metformin had no significant effect on birth weight percentile. 12 A study in 25 children exposed to metformin during the prenatal period reported higher fasting blood glucose and systolic blood pressure, but lower low-density lipoprotein cholesterol than children not exposed to metformin.…”
mentioning
confidence: 97%
“…21 However, the number of reports in which the possible endocrinedisrupting effects of metformin have been studied in humans are very limited, because most, still few, studies have focused on anthropometric measures of the offspring. [9][10][11][12][13] An in vitro study with human testes showed that metformin reduces testosterone production and testicular development. 22 A study from Finland reported no difference in testicular size between boys whose mothers had been treated with metformin during pregnancy and boys whose mothers had been treated with insulin.…”
mentioning
confidence: 99%